Entre o corpo e a teoria: a questão étnicoracial na obra e trajetória socioespacial de Milton Santos - CIRQUEIRA, Diogo Marcal (2010)
In this dissertation we analyze the ethnic-racial issue in the life and work of the geographer Milton Santos. We seek to understand this issue based on Milton Santos' literature and on his socio-spatial trajectory. Likewise, these factors are contextualize political, historical and geographically. We observe the impact of his intellectual formation and his experiences as a black person - in Brazil and in other countries in his analysis. Contrary to the assertion that Milton Santos never speak about this ethnicracial issue, we can identify some diversity and continuity in this approach, which, for didactic purposes, are divided into three periods: 1) the first moment of this production is between 1950 and 1964. The intellectual finishes his graduation in law in the "University of Bahia", becomes teacher in the High School of Ilhéus and ends his doctorate in geography in France. We highlight this period in the following books dealing of ethnic-racial issue: "O povoamento da Bahia" (1958) and "Marianne em preto e branco" (1960). 2) The second period is from 1964 until the end of the 1970s, time when Milton Santos is in exile. During this period the intellectual works as a Professor and researcher in countries of the "third world". We highlight the book "Manual de Geografia Urbana (1989), which deals with the existing ethnic and racial segregation in African cities. 3) The third moment occurs between the 1980s and 1990s, when Brazil completed the hundred years of "Proclamation of Abolition" (1988) and the 300 years since the death of Zumbi dos Palmares (1995). The intellectual granted several interviews on the theme and wrote several articles, especially in newspapers, where he treated the ethnic-racial relations. These texts discuss the concepts of nation, citizenship and "black body" in Brazil. Finally, we should emphasize that the analysis made by Milton Santos, in the light of his time and related by his personal experiences, were quite accurate. This demonstrates that the author was aware of the ethnic-racial problems, even this has not been the main focus of his theoretical analysis in the framework of geographical science.